Interplay between alveolar epithelial and dendritic cells and Mycobacterium tuberculosis. Issue 4 (3rd July 2020) - Rodrigues, Tamara Silva; Conti, Bruno José; Fraga-Silva, Thais Fernanda de Campos; Almeida, Fausto; Bonato, Vânia Luiza Deperon
Abstract: The innate response plays a crucial role in the protection against tuberculosis development. Moreover, the initial steps that drive the host-pathogen interaction following Mycobacterium tuberculosis infection are critical for the development of adaptive immune response. As alveolar Mϕs, airway epithelial cells, and dendritic cells can sense the presence of M. tuberculosis and are the first infected cells. These cells secrete mediators, which generate inflammatory signals that drive the differentiation and activation of the T lymphocytes necessary to clear the infection. Throughout this review article, we addressed the interaction between epithelial cells and M. tuberculosis, as well as the interaction between dendritic cells and M. tuberculosis . The understanding of the mechanisms that modulate those interactions is critical to have a complete view of the onset of an infection and may be useful for the development of dendritic cell-based vaccine or immunotherapies. Graphical Abstract: Epithelial cells and dendritic cells interaction with M. tuberculosis and implications for immunotherapy.